CORPORATE SUSTAINABILITY COMMUNICATION OF GREEN AND NON-GREEN COMPANIES IN DIGITAL ERA - Dhiba, Sintia Farach; Koan, Dianne Frisko (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2024)
This study aims to understand the corporate sustainability communication of green and non-green companies in Indonesia. This research examines 20 Indonesian companies divided into two subgroups of sample: green and non-green companies, which are classified according to their sustainability performance. The categorization indicator is obtained from CSRHub, a global database source aggregating Environmental, Social, and Governance (ESG) scores. The paper analyzes the implementation of formal communication channels and social media during two months (June-July 2023) as a novel digital communication channel at the stakeholder information strategy level. This study found green companies engaged in more active sustainability communication through formal and digital channels. In the formal communication, green companies routinely prepared standalone sustainability reports and annual reports reflecting sustainability values in each Board of directors' and commissioners' letters. In digital channels, green companies own social media accounts on many platforms to engage with stakeholders. Some of them have reflected their sustainability value publicly through the new media.